Bride price and the wellbeing of women - Sara Lowes; Nathan Nunn (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2017)
Bride price, which is payment from the groom and/or the groom's family to the bride's family at the time of marriage, is a common cultural practice in many African societies. It is often argued that the practice may have negative effects for girls and women because it may: incentivize early marriage and lead to higher fertility; promote the view that husbands have 'purchased' their wives, resulting is worse treatment of wives; and trap women in unhappy marriages due to the common requirement that some of the bride price be paid back upon divorce. We provide evidence towards a better understanding of the effects of bride price by examining the empirical relationship between bride price payments and various outcomes of interest. Examining a sample of 317 couples from the Democratic Republic of the Congo, we find no evidence that a larger bride price payment is associated with earlier marriage or with higher fertility. We also find that larger bride price payments are actually associated with better-quality marriages as measured by beliefs about the acceptability of domestic violence, the frequency of engaging in positive activities as a couple, and the self-reported happiness of the wife. We also examine the effect of the requirement for the bride price to be paid back upon divorce and find no evidence that this requirement is associated with women being less happy in their marriages on average. However, we do find that the combination of a very high bride price (over US1,000) and a requirement to pay back the bride price upon divorce is associated with lower levels of happiness for wives.
Keywords: J12; Z1; Z13; O55; 330; bride price; culture; marriage customs